S06.3 MSM Partner Services: What Works?. (13th July 2013) - Steben, M; Taylor, D; Cheuk, E
Abstract : Background: Partner notification (PN) is an important public health activity in STI control to stop onwward transmission. Various forms of PN services have been developed but not all have been evaluated to the same extent. In the era of evidence-based resource allocation, it is of utmost importance to focus limited resources on services shown to be the most efficient and effective. Methods: A review of the current literature and of the National Collaborating Centre for Infectious Diseases (NCCID) STBBI partner notification (PN) project productions was conducted. The impact of these various forms of PN services on disease incidence, re-infection, relationship status and healthcare costs will serve as efficiency and effectiveness markers. Results: Outcomes of MSM PN services has been measured and found to be associated with reduced index case GC and CT reinfection rates through patient delivered therapy, higher adoption of safer sexual practises in both index case and their partners, reduced incidence of STIs, higher rates of notification to long term partners and significant partners, high acceptability of face-to-face patient delivered partner notification in significant or long term relationships compared to higher acceptability of physician or electronic notification for casual or anonymous partnerships lower cost per case reached by patient referral compared to provider referral, lower levels of stress in relationships. Emotional and physical abuse after PN services can occur. The fears accompanying PN services can affect sexual spontaneity. Caution should be used before discarding PN services when efficiency or effectiveness is low because epidemiologic insight can still be gathered to help redirect screening activities. Conclusions: A Review of the evidence indicates that MSM PN services works!